3D reconstruction of the rat adrenal medulla. (19th June 2021) - Kemoklidze, Konstantin Gerbertovich; Tyumina, Natalia Andreevna; Leonenko, Pavel Sergeevich
Abstract: We performed 3D reconstruction of the microscopic structure of the adrenal medulla of the adult rats using serial histological sections with histochemical differentiation of adrenaline‐storing (A) and noradrenaline‐storing (NA) cells. Medulla volume is 1.18 ± 0.17 mm 3 . Chromaffin tissue consists of 82.9 ± 2.6% of A and 17.1 ± 2.6% of NA cells. Cords of the chromaffinocytes run along the nerves in the adrenal cortex and form cones when merging with medulla bulk. There is no unambiguously greater prevalence of A cells over NA in the areas of the medulla bordering on the cortex as compared to deep layers of medulla. NA cells form a network of beams. Their concentration increases with distance from the entry site of the nerves and is maximal on the opposite side. This testifies to the fallacy of the point of view about the disordered distribution of NA cells in the medulla. Based on the polar asymmetric arrangement of the adrenal chromaffin tissue, if it is necessary to completely remove the medulla with the keeping or reimplantation of the cortex, the subcapsular cortex zone located on the pole opposite to the entrance of nerves should be chosen. In addition, comparable results in the stereological examination of the medulla can be obtained only if taking its areas similar in location. The pronounced relationship in the arrangement of A and NA cells with nerves clearly indicates that in vivo nerve factors play a key role in differentiation and stabilization of the A and NA cells phenotypes.